Numerical studies of the effects of design parameters on flow fields in spiral concentrators - Ye, Guichuan; Ma, Liqiang; Alberini, Federico; Xu, Qian; Huang, Gen; Yu, Yuexian (International journal of coal preparation and utilization, 2022)
Spiral concentrators are widely used for the concentration of coal and heavy minerals. The design for the spiral concentrator is full of challenge because of the sensitivity of design parameters to water flow field. The study aims to reveal the rule of the design parameters on water flow field in spiral concentrators. The pitch, the transverse angle, and the flow rate were taken as the variables. A suggested simulation method based on grid independence investigation, four types of turbulence models, and Volume of Fluid (VOF) approach was proposed. The water flow field on spirals with different design parameters was determined by the validated model. The predicted water flow depth show agreement with the measured results. The Reynolds-Stress Model (RSM) turbulence model is superior to other turbulence models. The water depth and the primary velocity in spiral concentrators increase smoothly outward. The secondary velocity is relatively small compared with the primary velocity. No obvious secondary flow exists in the inner trough. The reversal position of the secondary flow is approximate at the fractional depth of 0.2 ~ 0.5. The reduction of the pitch and the flow rate, together with the increase of the transverse angle, can strengthen the secondary flow in spiral concentrators.